New BioRow™ oar angle guides - Kleshnev, V. (Rowing Biomechanics Newsletter, 2015)
The speed and results in rowing depend on the rower`s power, which is product of three components only: stroke rate, length and force. Everyone knows that rowing is faster at a higher rate with a longer stroke, whilst applying more force. Development of rowing electronics allowed us easy and reliable feedback on the stroke rate. Now it is a good time to take under control the stroke length, which is defined by the furthest handle positions and directly correspond to oar angles at the catch and finish.